Cytotoxic Activity of Ephedra alata Extracts on Human Lymphocytes and Breast Cancer Cell Line in Vitro - Mohammed, L. Z.; Mohammed, R. K. (Iraqi Journal of Science, 2023)
This study was conducted to use the local Ephedra alata plant as a model for extracting and detecting alkaloids in the stem of plant (alkaloids-rich extract and crude extract). Different extraction procedures were adopted for qualitative as well as the quantitative examination of the alkaloid extracts, as well as plant crude extract, the best methods for the extraction of the plant materials were applied. Simple, fast and accurate methods like TLC (thin layer chromatography) and HPLC (High-performance liquid chromatography), were used for the identification of the alkaloids (ephedrine) in different extracts of stems E. alata stems. Ephedrine alkaloid was detected in each alkaloids-rich and crude extracts of E. alata stems with 8 and 5 ppm concentrations respectively.The assessment of plant stems extract was carried out as these extracts have effects on human breast cancer cell lines (MDA-MB-231) and normal human lymphocytes (HLs). The study showed that there was no risk in using Ephedra in medicines as it has low cytotoxicity on HLs, while on MDA-MB-231 cell lines the percentage of cell death was 50.11% at a concentration 75mg/ml for crude extract after the 72-hours incubation period and the concentration of 15 mg/ml during the 24-hours incubation period had 50.63% inhibition rate.The study showed that E. alata, an important medicinal plant, has alkaloids-rich extracts that have low cytotoxic effects on cultured HLs, particularly when used at a concentration of 5 mg/ml considering its use at low concentrations, the local Ephedra alata plant has promising effects on cancerous lines.